Strain imaging to predict response to cardiac resynchronization therapy: a systematic comparison of strain parameters using multiple imaging techniques. (26th July 2018) - Zweerink, Alwin; van Everdingen, Wouter M.; Nijveldt, Robin; Salden, Odette A.E.; Meine, Mathias; Maass, Alexander H.; Vernooy, Kevin; de Lange, Frederik J.; Vos, Marc A.; Croisille, Pierre; Clarysse, Patrick; Geelhoed, Bastiaan; et al.
Abstract: Aims: Various strain parameters and multiple imaging techniques are presently available including cardiovascular magnetic resonance (CMR) tagging (CMR‐TAG), CMR feature tracking (CMR‐FT), and speckle tracking echocardiography (STE). This study aims to compare predictive performance of different strain parameters and evaluate results per imaging technique to predict cardiac resynchronization therapy (CRT) response. Methods and results: Twenty‐seven patients were prospectively enrolled and underwent CMR and echocardiographic examination before CRT implantation. Strain analysis was performed in circumferential (CMR‐TAG, CMR‐FT, and STE‐circ) and longitudinal (STE‐long) orientations. Regional strain values, parameters of dyssynchrony, and discoordination were calculated. After 12 months, CRT response was measured by the echocardiographic change in left ventricular (LV) end‐systolic volume (LVESV). Twenty‐six patients completed follow‐up; mean LVESV change was −29 ± 27% with 17 (65%) patients showing ≥15% LVESV reduction. Measures of dyssynchrony (SD‐TTPLV ) and discoordination (ISFLV ) were strongly related to CRT response when using CMR‐TAG ( R 2 0.61 and R 2 0.57, respectively), but showed poor correlations for CMR‐FT and STE (all R 2 ≤ 0.32). In contrast, the end‐systolic septal strain (ESSsep ) parameter showed a consistent high correlation with LVESV change for all techniques (CMR‐TAG R 2 0.60; CMR‐FT R 2 0.50; STE‐circ R 2 0.43; and STE‐long R 2 0.43). After adjustment for QRS duration and QRS morphology, ESSsep remained an independent predictor of response per technique. Conclusions: End‐systolic septal strain was the only parameter with a consistent good relation to reverse remodelling after CRT, irrespective of assessment technique. In clinical practice, this measure can be obtained by any available strain imaging technique and provides predictive value on top of current guideline criteria.